A bibliometric analysis of inventory management research based on knowledge mapping. Issue 1 (4th February 2019) - Ye, Yong; Ge, Yuanqin
Abstract : Purpose: The research mainly aims at the hotspot of inventory management by knowledge mapping and provides a visualization reference in this research field. Design/methodology/approach: First, inventory management journals during 1986 to 2017 were selected as the research object and text formatting in the Web of Science (WOS) database is exported. Then inventory management knowledge mapping is done and clustering keywords are extracted by using CiteSpace and VOSviewer software. Based on co-word analysis, the three special clusters are exported: inventory optimization strategy, inventory pricing and inventory technology. Besides, the clustering structure and time evolution are analysed. Finally, bibliographic item co-occurrence matrix builder (BICOMB) was used to extract the "journal" and "researchers" keywords in the inventory management research fields. Setting three parameters such as the cited half-life, centrality, frequency and keywords for data mining, it can infer the trend keywords of future research. Findings: Results showed that inventory management research has been abundant in literature over the past 30 years and has experienced a change from focusing on inventory optimization strategy to inventory pricing and inventory technology in process. It shows that inventory management research focused on the classic topics and includes economic order quantity, dynamic pricing, design and technology, and the new topics include channel coordination, hierarchical price and simulation. Research limitations/implications: Based on knowledge mapping, this study is still relatively macro and cannot cover all areas of inventory management. This study only investigated the state of correlational research in WOS and Google Trends and not additional databases. Originality/value: The current research mainly builds on knowledge mapping for the research hotspot of inventory management and provides visual references for future research in this field.